2006
DOI: 10.1007/s10750-006-0201-5
|View full text |Cite
|
Sign up to set email alerts
|

Hunger-induced foraging behavior of two cyprinid fish: Pseudorasbora parva and Rasbora daniconius

Abstract: The feeding and swimming behaviors of Pseudorasbora parva and Rasbora daniconius (Cyprinidae) with two different prey types (Daphnia pulex and Artemia salina) at different densities (0.5, 1, 2, 5, 10, or 25 per l) were studied after 36 h of food deprivation. Full satiation was defined as the cumulative number of attacks performed until fish attain a constant attack rate which for P. parva was 425 and R. daniconius was 390 attacks. Initial feeding rates showed marked variation with prey availability. Feeding ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Further, a high feed delivery rate may reduce an individual's swimming speeds during feeding, as fish switch from swimming to processing and handling prey as feed encounter rate increases (e.g. Priyadarshana et al 2006). In addition, increases in long-term EMG profiles (obtained via an EMG transmitter calibrated using a hard-wired EMG during U crit tests) were also observed as consequences of the administration of Fish Physiol Biochem (2012) 38:17-41 25 three diet formulations (organic vs. conventional) (Carbonara 2009) and in experiments evaluating the consequences of starvation (McFarlane et al 2004).…”
Section: Individual Swimming Behaviourmentioning
confidence: 99%
“…Further, a high feed delivery rate may reduce an individual's swimming speeds during feeding, as fish switch from swimming to processing and handling prey as feed encounter rate increases (e.g. Priyadarshana et al 2006). In addition, increases in long-term EMG profiles (obtained via an EMG transmitter calibrated using a hard-wired EMG during U crit tests) were also observed as consequences of the administration of Fish Physiol Biochem (2012) 38:17-41 25 three diet formulations (organic vs. conventional) (Carbonara 2009) and in experiments evaluating the consequences of starvation (McFarlane et al 2004).…”
Section: Individual Swimming Behaviourmentioning
confidence: 99%
“…accrue greater energy reserves which would help them survive periods of food shortage and/or adopt an active foraging behavior). Secondly, we explored the effects of limited food on the growth and survival when fish could actively search for food, thereby allowing appetite stimulated activity to interact with stressful nutritional conditions (Priyadarshana et al 2006). Thirdly, because selection would act on more than physiological capacity to endure starvation (Schluter et al 1991;Grant and Grant 2002), we added social interactions, both competition among genotypes and predation risk, allowing us to evaluate the outcome of interactions between competitive ability, swimming activity, and risk-taking behavior of transgenic and wild fish under stressful nutritional conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fish often live in variable environments in which conditions such as food availability change profoundly, and are significantly correlated with growth, SMR and/or behavioural traits (Killen et al, 2011;Priyadarshana et al, 2006;Auer et al, 2016b). Typically, fish show high food consumption and thus faster growth rates when food availability is high (Dibattista et al, 2006;Auer et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, behavioural traits vary with food availability; however, the relationship varies among studies. For example, a study in Pseudorasbora parva and Rasbora daniconius found that individuals performed more foraging behaviours (and were more active and aggressive) when food resources were lacking (Priyadarshana et al, 2006), whereas a study of rainbow trout (Oncorhynchus mykiss) found that individuals performed more risktaking behaviours under conditions of food abundance (Biro et al, 2006). These physiological and behavioural responses to food availability and their ecological consequences are vital adaptations of fish in the natural environment.…”
Section: Introductionmentioning
confidence: 99%